RESPON JAGUNG MANIS (Zea mays saccharata Stut ) TERHADAP DOSIS DAN JENIS PUPUK ORGANIK - Zulkifli Zulkifli; Herman Herman (Jurnal Agroteknologi, 2012)
Organic farming is a natural farming in practice trying to avoid the use of chemicals and fertilizers that are poisoning the environment. Organic fertilizer from manure (cow, buffalo, goats, chickens, ducks) and agricultural waste (leaves, straw, corn stalks and husks) (Anonemus, 2004). Mustari, K (2004), plant wastes can be used as fertilizer bokasi by mixing the waste with Effective Micro-organism-4 ( EM4 ) . The study aims to determine the effect of dose and type of organic fertilizer in a single interaction and the Sweet Corn Crop. This research used Completely Randomized Design (CRD), factorial with treatments as follows; dose of organic fertilizer that consists of 4 (four) D1. ¼ sacks doses or 200 grams each plot, D2. ½ sacks doses or 400 grams bokasi each plot, D3. ¾ sacks doses or 600 grams bokasi each plot, D4. doses or 800 grams 1.0 sacks bokasi each plot and type of organic fertilizer consisting of J1. cow manure, J2. goat manure, J3. chicken manure and J4. Bokasi fertilizer. Parameters were observed among other stem diameter (cm), leaf area and length of cob (cm). From these results it can be concluded that the best treatment is D2J4 namely; bokasi doses of 400 grams per plot, with the cob diameter 1.8 cm, 6354.14 cm2 leaf area and length of 20.73 cm cob without cornhusk.